2012
DOI: 10.3346/jkms.2012.27.5.518
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Waist Circumference According to Glucose Tolerance Status in Korea: The 2005 Korean Health and Nutrition Examination Survey

Abstract: The purpose of this study was to investigate the stage of glucose intolerance in which persons showed a maximum obesity in Korea. A total of 4,479 participants, who were involved in the 2005 Korean National Health and Nutrition Examination Survey, was examined. The participants were divided into 5 groups by fasting plasma glucose (FPG); normal fasting glucose (NFG)1, FPG < 90 mg/dL; NFG2, FPG 90-99 mg/dL; impaired fasting glucose (IFG)1, FPG 100-109 mg/dL; IFG2, FPG 110-125 mg/dL; and diabetes mellitus, FPG ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
2
0
1
Order By: Relevance
“…The association of obesity with hyperglycemia is well established 29 ; obesity is one of the strongest and most important risk factors for type 2 diabetes. 30 Previous studies have demonstrated strong, positive associations of BMI with fasting glucose and HbA1c with both prediabetes and diabetes, 31 32 consistent with our results. The inverse associations of BMI with glycated albumin and fructosamine in persons without diagnosed diabetes and the U-shaped associations in the overall population are in contrast to this literature.…”
Section: Discussionsupporting
confidence: 92%
“…The association of obesity with hyperglycemia is well established 29 ; obesity is one of the strongest and most important risk factors for type 2 diabetes. 30 Previous studies have demonstrated strong, positive associations of BMI with fasting glucose and HbA1c with both prediabetes and diabetes, 31 32 consistent with our results. The inverse associations of BMI with glycated albumin and fructosamine in persons without diagnosed diabetes and the U-shaped associations in the overall population are in contrast to this literature.…”
Section: Discussionsupporting
confidence: 92%
“…Weight gain has been reported to decrease response to insulin and is associated with an increased risk of developing diabetes, suggesting that the association between obesity and diabetes is indisputable. A study based on the general Korean population reported that degree of BMI was increased with FPG levels b100 mg/dl, peaked with FPG levels of 100-109 mg/dl, and then plateaued with higher FPG levels [16]. The mean FPG levels in the subjects in the IFG group were 107.89 mg/dl (men) and 106.43 mg/dl (women); in accordance with that study, the IFG group in our study showed higher body weight, BMI, and WC than the NFG group.…”
Section: Discussionmentioning
confidence: 98%
“…Forsberg et al stated that the peripheral neuropathy was strongly associated with oxidative stress and inflammatory markers, confirming our results and proving the role of oxidative stress in driving progression of T2DM and in mediating complications associated with the disease [ 23 ], thus the modulation of oxidative stress represents an important target for therapeutic intervention. It was proved that severe oxidative stress in T2DM with increased BMI has been associated with hyperglycemia, glycemic control, insulin resistance and disease duration [ 24 26 ]. However, the positive association of oxLDLc with incident T2DM, was attenuated after adjustment for BMI [ 27 ].…”
Section: Discussionmentioning
confidence: 99%